2011
DOI: 10.1007/s00572-011-0397-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the root-knot nematode [Meloidogyne incognita (Kofoid & White) Chitwood] on tomato by dual inoculation with arbuscular mycorrhizal fungi and plant growth-promoting rhizobacteria

Abstract: Arbuscular mycorrhizal (AM) fungi and plant growth-promoting rhizobacteria (PGPR) have potential for the biocontrol of soil-borne diseases. The objectives of this study were to quantify the interactions between AM fungi [Glomus versiforme (Karsten) Berch and Glomus mosseae (Nicol. & Gerd.) Gerdemann & Trappe] and PGPR [Bacillus polymyxa (Prazmowski) Mace and Bacillus sp.] during colonization of roots and rhizosphere of tomato (Lycopersicon esculentum Mill) plants (cultivar Jinguan), and to determine their comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 28 publications
1
14
0
6
Order By: Relevance
“…or Bacillus polymyxa) than with any of the microorganisms alone. Similarly, incidence of the root-knot nematode Meloidogyne incognita in tomato was reduced most efficiently after co-inoculation of an AM fungi with PGPR (Liu et al, 2012).…”
Section: Functions Of Beneficial Microbes and Similarities To Pathogensmentioning
confidence: 96%
“…or Bacillus polymyxa) than with any of the microorganisms alone. Similarly, incidence of the root-knot nematode Meloidogyne incognita in tomato was reduced most efficiently after co-inoculation of an AM fungi with PGPR (Liu et al, 2012).…”
Section: Functions Of Beneficial Microbes and Similarities To Pathogensmentioning
confidence: 96%
“…Conversely, the impact of the co-inoculation of bacterial and fungal interaction on plants under abiotic stresses, including metal toxicity, is rarely studied. The impacts of the synergistic interaction between fungi and bacteria are reported to be beneficial for plant growth promotion by Liu et al (2012) , as the survivability, growth, and development of Verbascum lychnitis under Zn and Pb substrates were significantly improved by co-inoculating it with endophytic and AM fungi ( Wężowicz et al, 2017 ). Similarly, the positive effects of reduced excess zinc toxicity and modulated micronutrient uptake in Glycine max L. have been observed with the combined inoculation of AM Gigaspora rosea and rhizobacterium Bradyrhizobium diazoefficiens by Ibiang et al (2017) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AM fungus R. intraradices (formly G. intraradices ) was found to significantly decrease the concentration of organophosphate insecticide named phoxim in shoots and roots of carrot and green onion (Wang et al 2011). Liu et al (2012a) demonstrated that dual inoculation of specific AM fungi and plant growth-promoting rhizobacteria (PGPR) could stimulate each other and that the combination of G. mosseae (syn. F. mosseae ) and PGPR Bacillus sp.…”
Section: Mycorrhizal Functionmentioning
confidence: 99%